Metabolic interaction between urea cycle and citric acid cycle shunt: A guided approach. Issue 2 (15th December 2017) - Pesi, Rossana; Balestri, Francesco; Ipata, Piero L.
Abstract: This article is a guided pedagogical approach, devoted to postgraduate students specializing in biochemistry, aimed at presenting all single reactions and overall equations leading to the metabolic interaction between ureagenesis and citric acid cycle to be incorporated into a two‐three lecture series about the interaction of urea cycle with other metabolic pathways. We emphasize that citrate synthetase, aconitase, and isocitrate dehydrogenase, three enzymes of the citric acid cycle are not involved, thus creating a shunt in citric acid cycle. In contrast, the glutamic‐oxaloacetate transaminase, which does not belong to citric acid cycle, has a paramount importance in the metabolic interaction of the two cycles, because it generates aspartate, one of the two fuel molecules of urea cycle, and a‐ ketoglutarate, an intermediate of the citric acid cycle. Finally, students should appreciate that balancing equations for all atoms and charges is not only a stoichiometric task, but strongly facilitates the discussion of the physiological roles of metabolic pathways. Indeed, this exercise has been used in the classroom, to encourage a deeper level of understanding of an important biochemical issue. © 2017 by The International Union of Biochemistry and Molecular Biology, 46(2):182–185, 2018.